Editor's Choice – Prognostic Role of Pre-Operative Symptom Status in Carotid Endarterectomy: A Systematic Review and Meta-Analysis. (April 2020) - Ball, Stephen; Ball, Alexandra; Antoniou, George A.
Abstract : Objective: This study investigates the prognostic significance of pre-operative symptom status and type of symptom in outcomes after carotid endarterectomy (CEA). Methods: This review was conducted and reported in accordance with the Preferred Reporting Items for Systematic reviews and Meta-analysis (PRISMA) to identify studies reporting peri-operative outcomes of CEA in symptomatic and asymptomatic patients. The last search was conducted in August 2019 and a methodological assessment was performed using the Newcastle Ottawa Scale. A meta-analysis of outcome data using the odds ratio (OR) as the summary statistic was conducted, and the precision of the effect was reported as 95% confidence interval (CI). Fixed effect or random effects models were used to calculate the pooled estimates. Results: Eighteen studies reporting a total of 91 895 patients were included in the meta-analysis. Asymptomatic patients had a lower peri-operative risk of stroke (OR 0.5, 95% CI 0.45–0.54; p  < .001) and death (OR 0.66, 95% CI 0.57–0.77; p  < .001) than symptomatic patients, but the risk of myocardial infarction was not significantly different (OR 0.98, 95% CI 0.84–1.15; p  = .82). Those suffering a pre-procedural stroke had an increased peri-operative risk of stroke and death vs. patients suffering a pre-procedural transient ischaemic attack or amaurosis fugax. Conclusion: Patients undergoing CEA after a stroke have worse peri-operative outcomes in terms of stroke and death. Further research needs to be performed to ascertain the value of this finding in risk stratification systems and to investigate potential aetiological associations between pre-operative symptom status and peri-operative risk following a CEA.